Different Stability-Indicating Chromatographic Techniques for the Determination of Netobimin - Nesrin K. Ramadan; Afaf O. Mohamed; Sara E. Shawky; Maissa Y. Salem (Journal of Analytical Methods in Chemistry)
Two simple, accurate, and sensitive methods were developed for the determination of netobimin in the presence of its degradation product. Method (A) was an HPLC method, performed on C18 column using acetonitrile/methanol/0.01 M potassium dihydrogen phosphate (56 : 14 : 30 by volume) as a mobile phase with a flow rate of 0.5 mL/min. Detection was performed at 254 nm. Method (B) was a TLC method, using silica gel 60 F254 plates; the optimized mobile phase was toluene/methanol/chloroform/ammonium hydroxide (5 : 4 : 6 : 0.1 by volume). The spots were scanned densitometrically at 346 nm. Linearity ranges were 1–10 μg/mL for method (A) and 0.5–5 μg/band for method (B), and the mean percentage recoveries were 99.3±0.7% and 99.7±0.7% for methods (A) and (B), respectively. The proposed methods were found to be specific for netobimin in the presence of up to 90% of its degradation product. Statistical comparison between the results obtained by these methods and the manufacturer method was done, and no significance difference was obtained.